On Grid Numbering and Translational Number as Two New Techniques in Multiplication - S. Chususiyah; Dafik Dafik; O A Safiati (Pancaran Pendidikan, 2019)
The multiplication operation in maths is still considered to be difficult by school students. Despite, multiplication is one of the most important topics in mathematics learning, since this operation is taught from elementary to secondary school levels, and we often encounter its application in everyday life. In the learning process, the multiplication operations will not only develop mathematical numeracy skills, understanding multiplication will also have an impact on the growth of students' critical thinking skills. Therefore, the basic concepts related to multiplication operations in mathematics must be taught fundamentally by the students, thus they can take advantage of it later on in their daily life.